TANTANGAN INTERNALISASI NILAI-NILAI SEJARAH PENDIDIKAN ISLAM DALAM KEGIATAN PEMBELAJARAN MAHASISWA PAI DI IAIH PARE - Ahmad Rusydi; Fatahuddin; Didik Andriawan (PT. Saha Kreasi Indonesia, 2025)
This study aims to analyze the challenges in internalizing the historical values of Islamic education (SPI) in the learning activities of Islamic Religious Education (PAI) students at the Hasanuddin Islamic Institute (IAIH) in Pare. This study uses a qualitative method with a case study approach. Data collection techniques were carried out through in-depth interviews, participant observation, and documentation studies of PAI students selected purposively. The results of the interviews revealed several major challenges in internalizing SPI values, including the emergence of an individualistic culture among students, low intrinsic motivation to deepen SPI values, and the influence of globalization that hinders the process of instilling values. The research findings indicate that although students have understood SPI values cognitively, internalization in the form of honesty, responsibility, discipline, and spirituality still faces significant obstacles. This study recommends strengthening the guidance system, optimizing the campus environment, and innovating value-based learning methods to optimize the internalization of SPI values in the learning activities of PAI students at IAIH in Pare.